Virtually connected in a multiverse of madness?: Perceptions of gaming, animation, and metaverse - Oliveira, A.; Cruz, M. (Human activity recognition (HAR) in healthcare, 2024)
Few studies analyze what are the common representations of the Metaverse. Regarding 8 what has been said about this concept, our research aims to verify how adults’ percept and represent 9 the Metaverse. We carried out a study with focus groups, having as participants Portuguese adults 10 all considered habitual gamers (or users of digital games). The objectives for this study were seven: 11 verify how the Metaverse is being represented and characterized; identify which technologies that 12 stimulate the immersion experience; identify the main dimensions that influence the acceptance of 13 the Metaverse concept; understand the perceptions of Metaverse and virtual reality regarding 14 socialization and well-being; verify the perceptions of a gamer’s daily lives regarding the Metaverse, 15 virtual reality, and gaming concepts; understand the impact of social representations on the 16 gaming concept; to understand the perceived role of animation regarding the Metaverse, virtual 17 reality, and gaming concepts. Our results reveal a common understanding of the Metaverse, despite 18 some confusion about this concept. We also verified the high importance of well-being and social 19 dimensions in the Metaverse immersive experiences provided by technology or gaming 20 characteristics. This exploratory study gave us essential findings about the perceptions of the 21 Metaverse and a deep understanding of the relations between Metaverse, virtual reality, animation, 22 and gaming.